Charecterisation of Palm Oil Empty Fruit Bunch (POEFB) fiber via enzyme treatment - Sanmugam, Kumanan (2013)
Lignocelluloses based natural fiber is being used as an alternative to traditional glass and carbon fiber in the composite materials due to its low density and higher specific properties. These reinforced plastics have got prospective applications in various sectors, including construction materials such as windows, sidings and roof tiles, grain and fruit storage and footwear, car door panel, consoles, seat backs, packaging and so on One of the natural fibers considered is palm oil empty fruit bunches (POEFB) fibers which offer advantages such as availability, renewability, low cost and the established technology to extract the fibers. POEFB is easily obtainable as wastage from palm oil industries but has not yet been fully materialized in the fabrication of biodegradable composites. The current work is focused on the treatment of POEFB fiber with enzyme. Surface modifications for better adhesion between fiber and matrix were carried out by Laccase enzyme treatment. Enzyme treatment here was analyzed by placing 2 mg of Laccase enzyme in 4 beakers and the POEFB is treated for 2,4,6 and 8 hours simultaneously. The POEFB fiber is then analyzed via Lignin test, water absorption test and tensile test. It was determined that 4 hour treated fiber presented a higher lignin lost and a significant increase in mechanical properties.